Identifikasi Protozoa Usus Oportunistik dan Faktor Risikonya Pada Anak Panti Asuhan Kota Pekanbaru - Esy Maryanti; M. Reyhan Ahza Hamidy; Lilly Haslinda (Fakultas Kedokteran Universitas Riau, 2019)
Opportunistic intestinal protozoa are protozoa that can infect humans at a time when the body’s defense system is declining (immunocompromising). Opportunistic protozoan infections are infections by intestinal protozoa that were not previously considered important, but now can cause disease in humans. Opportunistic intestinal protozoan infections besides being found in immunocompromised patients are also reported to infect children. Some of the intestinal protozoan species that have been identified to cause infection are Cryptosporidium sp, Isospora belii, Cyclospora sp, and Blastocystis hominis. This study was an analytical study with a cross sectional design conducted in June 2018 until January 2019. In this study, modified Ziehl-Neelsen staining was used and the results were 25.6% of orphanages infected with opportunistic intestinal protozoa, which consisted of Cryptosporidium sp. as much as 14.1%, Blastocystis hominis as much as 4.6%, infection with a mixture of Cryptosporidium sp and Blastocystis hominis as much as 4.6%, Isospora belii as much as 2.3%, and no infection by Cyclospora cayetanensis. There was no association between opportunistic intestinal protozoan infections with poor handwashing habits, bowel habits, food hygiene, drinking water treatment, and bad animal raising habits.